Medications for Short-Course Chemotherapy of Drug Resistant Tuberculosis and Their Effect on the Host - G. N. Mozhokina; A. G. Samoylova; I. A. Vasilyeva; A. E. Russkikh (Туберкулез и болезни лёгких)
The review presents up-to-date data from 88 publications devoted to the short-course regimens of multiple drug resistant tuberculosis treatment and describes characteristics of the most effective drugs – bedaquiline, linezolid, delamanid, and clofazimine. Information is also provided on the additional properties of the drugs, i.e. modulation of the key immune response and immunometabolic processes that underlie a new approach to improvement of tuberculosis treatment, the so-called host therapy.